تطوير أداة لتقويم كتب تعليم اللغة العربية للناطقين بغيرها لكل مستوى تعليمي - كيومية، ليلى بنت محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study aims to provide a model for evaluation of Arabic teaching books for non-native speakers at each education level (beginner, intermediate, and advanced). To conduct this study, the researcher used the descriptive and analytical approaches by reviewing a range of sources related to criteria for evaluating books on language teaching. A standard questionnaire was prepared to evaluate the Arabic teaching books for non-native speakers; this questionnaire was scrutinised by some Arabic language experts to customize the standards for each education level. After analysing the experts' opinions, the study came up with three evaluation instruments, namely an instrument to evaluate the Arabic teaching books for non-native speakers at the beginner level, which consisted of 133 sub-standards divided into nine main areas of evaluation and 19 elements of evaluation, and an instrument to evaluate the Arabic teaching books for non-native speakers at the intermediate level, which consisted of 187 sub-standards divided into ten main areas of evaluation, and 23 elements of evaluation was also created. In addition, an instrument to evaluate the Arabic teaching books for non-native speakers at the advanced level, which consisted of 171 sub-standards divided into ten main areas of evaluation, and 23 elements of evaluation. In addition, each standard has three evaluations of estimates, namely (0-2), 2 representing the top grade while 0 representing the lowest grade. The books were evaluated according to those evaluations of estimates. Determining the rectifiers evacuated of any digital estimates are best suited for the development of the books. This study provides a more accurate and precise approach in the evaluation of the Arabic teaching books for non-native speakers according to their educational level.